2014
DOI: 10.1371/journal.pone.0086467
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of 25-Hydroxyvitamin D among Chinese Breast Cancer Patients

Abstract: BackgroundFew studies have investigated vitamin D status in association with modifiable lifestyle factors and clinical characteristics among breast cancer patients, with no studies among Chinese women, who may be at higher risk of vitamin D deficiency. We aimed to evaluate circulating 25-hydroxyvitamin D (25(OH)D) levels in association with clinical and lifestyle factors among 1,940 Chinese breast cancer patients.MethodsParticipants included breast cancer cases aged 22–77 from a population-based case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
2
18
0
4
Order By: Relevance
“…This study showed that there was no association of vitamin D with tumor characteristics, ER or PR status or stage of breast cancer which is consistent with similar findings in a Chinese population [98]. It is in contrast with research finding of an association of high 25(OH)D concentrations with lower tumor size at early breast cancer diagnosis [99] or ER/PR status of tumor [100].…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that there was no association of vitamin D with tumor characteristics, ER or PR status or stage of breast cancer which is consistent with similar findings in a Chinese population [98]. It is in contrast with research finding of an association of high 25(OH)D concentrations with lower tumor size at early breast cancer diagnosis [99] or ER/PR status of tumor [100].…”
Section: Discussionsupporting
confidence: 87%
“…However, no studies have shown that having early-stage undiagnosed cancer affects 25 (32). A later study in China supported those results (33). Because most breast cancer tumors are diagnosed at stages I and II, most CC studies should not be subject to a cancer effect on 25(OH)D concentration.…”
Section: Resultsmentioning
confidence: 98%
“…Dietary factors associated with increased BC risk included intake of total n-6 polyunsaturated fatty acids (PUFA) (Kiyabu et al, 2015), vitamin D deficiency or insufficiency (Shi et al, 2014a;Park et al, 2015a), high levels of serum cadmium (Nagata et al, 2013;Itoh et al, 2014;Ding et al, 2015), high intake of salt (Park et al, 2014b), sugar (Sulaiman et al, 2014), meat (Ko et al, 2013), and saturated fat and oils (Balasubramaniam et al, 2013;Wang et al, 2013a). In women with BC, the trace elements, cadmium, magnesium, copper, cobalt and lithium, were found in high levels.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…High consumption of fruits and vegetables was associated with decreased BC risk (Sangrajrang et al, 2013), and high intake of fatty foods was associated with increased BC risk (Balasubramaniam et al, 2013;Wang et al, 2013a). Data suggested that an intake of vitamin D, dietary fiber and intake of plant-and soy-based products may be protective for BC (Ko et al, 2013;Li et al, 2013a;Wada et al, 2013;Shi et al, 2014a;Sulaiman et al, 2014;Wang et al, 2014a;Park et al, 2015a), whereas high intake of dietary salt, sugar and meat may increase the risk of BC (Ko et al, 2013;Park et al, 2014b;Sulaiman et al, 2014).…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%